Influence Of Opposed Right _ Turns On Saturation Flow At Signalised Intersection - jany agustin (Jurnal Jalan-Jembatan, 1987)
The objective of the project was to sunday the influence of apposed right - truns on saturation flow it was intended to useas a tool for design and timing of signalised intersection because on guidance procedure was avaible in Indonesia.